2017
DOI: 10.1093/jisesa/iex087
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Molecular and Conventional Methods for Estimating Parasitism Level in the Pomegranate Aphid Aphis punicae (Hemiptera: Aphididae)

Abstract: Aphidiinae (Braconidae: Aphidiinae) is a subfamily of endoparasitic wasps specialized in parasitizing aphids. Although, to date, different methods have been used to measure parasitism level, obtaining an accurate estimate remains challenging due to several limiting factors. This study was set to: 1) Compare efficiency of conventional and molecular-based methods in estimating parasitism level of the pomegranate aphid Aphis punicae (Passerini; Hemiptera: Aphididae), and 2) Estimate seasonal activity of the Aphid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
(52 reference statements)
1
4
0
Order By: Relevance
“…The main advantages of the DNA barcoding technology include detecting immature parasitoids inside their aphid hosts and early, accurate, and effective monitoring of parasitism levels in aphids. 18,19,40 In the present study, we found that the COI barcode primers could efficiently amplify the target region from adult parasitic wasp samples as well as from S. miscanthi in mummified aphid and nonparasitized aphid samples. Thus, COI cannot be used for the unambiguous detection of immature parasitoids inside their S. avenae or S. miscanthi hosts.…”
Section: Discussionsupporting
confidence: 52%
“…The main advantages of the DNA barcoding technology include detecting immature parasitoids inside their aphid hosts and early, accurate, and effective monitoring of parasitism levels in aphids. 18,19,40 In the present study, we found that the COI barcode primers could efficiently amplify the target region from adult parasitic wasp samples as well as from S. miscanthi in mummified aphid and nonparasitized aphid samples. Thus, COI cannot be used for the unambiguous detection of immature parasitoids inside their S. avenae or S. miscanthi hosts.…”
Section: Discussionsupporting
confidence: 52%
“…It is important to follow good barcoding practices [50] to minimise the risk of finding nonpermissible interactions, or 'false positives', due to contamination. As such, we do not advocate the complete replacement of traditional rearing approaches with molecular techniques, rather that these approaches are complementary, and that rapid assessment with metabarcoding may serve as a useful indicator of where traditional rearing and morphological taxonomy efforts should be targeted [56]. In fact, the continued efforts of traditional taxonomists, particularly in the discovery and naming of species, rather than being devalued by the popularity of molecular approaches, should be considered essential for their successful application.…”
Section: Trends In Parasitologymentioning
confidence: 99%
“…Accordingly, various molecular methods of characterization for microbes are extensively described in several review articles and books (Dickinson, 2005;Tsiamis et al 2014;Awasthi, 2015). The combined use of various conventional and molecular methods have been described mostly for the characterization of microorganism (Spiegelman et al, 2004;Martinelli et al, 2015;Cui et al 2018, Franco-Duarte et al, 2019 and insects (Farrokhzadeh et al, 2017).…”
Section: Comparison or Combined Use Of Conventional And Molecular Metmentioning
confidence: 99%